2020
DOI: 10.5430/wje.v10n1p42
|View full text |Cite
|
Sign up to set email alerts
|

Financial Situation of College Students

Abstract: The aim of the study was to determine the financial well-being of university students in sports education according to their gender, age, grade/class, education department and residence (place to live). Total 654 college studentsn (M, age=21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…German male students scored higher than female students did. No gender differences were found (Herdjiono et al, 2018;Yasar, Turğut, 2020).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…German male students scored higher than female students did. No gender differences were found (Herdjiono et al, 2018;Yasar, Turğut, 2020).…”
Section: Introductionmentioning
confidence: 80%
“…Other studies showed that men obtained better results than women in financial knowledge (Falahati, Paim, 2011;Khurshed, Iftikhar, 2014;Yaringaño, 2018). Regarding financial perception, men came out better than women (Yasar, Turğut, 2020). Recently, in the work of Happ, Hahn, Jang and Rüter (2022), which they carried out in Germany, they found a gender difference, but not in Korea, whose results were different.…”
Section: Introductionmentioning
confidence: 93%
“…Gender disparities in personal finance does not stop at the educational level but was also found for financial confidence. Yasar and Turgut (2020) studied the financial status of college students in Turkey and found no significant difference by gender. They did find, however, that female participants viewed their financial situation as being much worse than their male counterparts.…”
Section: Gender Effectsmentioning
confidence: 99%
“…The tertiary education years are characterized by many potential stressors, such as housing conditions and financial problems (Flett et al, 2009;Tosevski et al, 2010;Yasar and Turgut, 2020), and, for many students, this is their first experience away from their family, which may make adapting to a new social context even more difficult (Monti et al, 2013). Moreover, students often have to face increased study demands, and, therein, a greater pressure to succeed, feelings of inadequacy, competition with peers, and insecurity about the future (Macaskill, 2013;Kreß et al, 2015).…”
Section: Introductionmentioning
confidence: 99%